2021
DOI: 10.1016/j.actbio.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-oxidative and ROS scavenging properties of biomaterials coated with epigallocatechin gallate for tissue engineering

Abstract: In tissue engineering, excessively generated reactive oxygen species (ROS) during biomaterial implantation or cell transplantation is a one of major causes of diminishing therapeutic effects. In this study, we prepared biomaterial surfaces coated with antioxidant epigallocatechin gallate (EGCG) and metal ions, and evaluated their anti-oxidative and ROS scavenging properties. We revealed that EGCG-coating on polycaprolactone (PCL) film surface increased hydrophilicity and anti-oxidative properties as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…They found that EGCGcoated polycaprolactone (PCL) film increases cell attachment, viability, and proliferation of human adipose-derived stem cells (hADSCs) against H 2 O 2 exposure while regulating cell signalling that diminishes apoptotic genes, thus augmenting the expression of the anti-oxidative enzyme. The amalgamated EGCG-coated PLLA fibre spheroids showed better cell viability and anti-oxidative activities in response to H 2 O 2 induced oxidative stress compared to the control [53].…”
Section: Epigallocatechin Gallate (Egcg) Treatments For Wound Healingmentioning
confidence: 89%
See 3 more Smart Citations
“…They found that EGCGcoated polycaprolactone (PCL) film increases cell attachment, viability, and proliferation of human adipose-derived stem cells (hADSCs) against H 2 O 2 exposure while regulating cell signalling that diminishes apoptotic genes, thus augmenting the expression of the anti-oxidative enzyme. The amalgamated EGCG-coated PLLA fibre spheroids showed better cell viability and anti-oxidative activities in response to H 2 O 2 induced oxidative stress compared to the control [53].…”
Section: Epigallocatechin Gallate (Egcg) Treatments For Wound Healingmentioning
confidence: 89%
“…Inhibit nuclear factor-kappa B (NF-κB) transcription [12,27,30] Inhibit (NF-κB) protein factors [12,30] Inhibit IL-8 production [50] Inhibit LPS-induced inflammation [51,52] Block Notch signaling [51] Antioxidant Inhibit nitric oxide formation [19] Inhibit ROS enzymes [53] Activation of SOD [54] Anti-scarring Inhibit TGF-β receptor [27] lymers 2021, 13, 3656 8 of 16…”
Section: Anti-inflammatorymentioning
confidence: 99%
See 2 more Smart Citations
“…ROS in physiological amount is needed for cellular signal transduction and physiological metabolism. However when the generation of ROS exceed the antioxidant capacity, oxidative stress develop and normal tissue haemostasis imbalance occur leading to poor tissue regeneration and wound healing ( Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%